Deller’s Café - Cleave, Paul (Petits Propos Culinaires, 2010)
We tend to think of the history of restaurants in terms of grand hotels, West End watering holes and the like. This photo-essay (based on historic postcards) reminds us how much capital in Britain was invested during the inter-war years in feeding classes of people who were unfamiliar with haute cuisine or European cooking.